مستقبل قطاع الجلود في مصر في ظل استراتيجية المجتمعات الصناعية المتكاملة: دراسة جدوى اقتصادية - خليل، إمام; حسن، إسلام عبدالسلام رجب علي Hasan, Islam Abdulsalam Rajab Ali (جامعة مدينة السادات - كلية التجارة, 2020)
The Egyptian industrial activities has comparative advantages, but this advantage did not lead these industries to a competitive position on the map of emerging economies, because Egyptian industrial sector suffers from weakness on interrelationships between its sectors and weak networking between industrial activities, while the strategy of integrated industrial societies On the establishment of industrial clusters, and industrial alliances may help to reduce production costs and Maximize the utilization of comparative advantages in the industrial sector and convert them into competitiveness advantages ,also the integrated industrial societies is created for each industrial activity that have same value chain. The problem of research is integrated industrial societies can be used to treat the imbalance in Egyptian industrial sector because this strategy depend on industrial clusters to plan small and medium enterprises with the application on the leather sector in Egypt. A preliminary feasibility study to serve the idea of research, and the research aims to identify how to reach integrated industrial Societies in application on the leather sector in Egypt. The research examines the hypothesis that say strategy of industrial clusters and strategic alliances can be used to reach "integrated industrial societies" that support the competitiveness of the leather sector. The results came to prove the validity of the hypothesis and recommended following the proposal presented in the research in industrial planning.
على الرغم من تمتع الأنشطة الصناعية المصرية بمزايا نسبية إلا أن هذه الميزة لم تؤدي بتلك الصناعات إلى موقع تنافسي على الخريطة الاقتصاديات الناشئة، وذلك كنتيجة لما يعاني منه القطاع الصناعي المصري من غياب العلاقات الترابطية بين قطاعاته وضعف العلاقات التشابكية بين الأنشطة الصناعية، في حين تقوم استراتيجية المجتمعات الصناعية المتكاملة على إنشاء عناقيد صناعية في ضوء مجموعة من التحالفات الصناعية التي تساعد في تخفيض تكاليف الإنتاج تعظيم الاستفادة بالمزايا النسبية في القطاع الصناعي وتحويلها إلى مزايا تنافسية بحيث ينشأ مجتمع صناعي متكامل لكل نشاط صناعي له نفس سلسلة القيمة، ويمكن مشكلة البحث في أنه يمكن استخدام المجتمعات الصناعية المتكاملة في علاج هذه الجوانب من القصور والتي تعتمد على استراتيجية العناقيد الصناعية لتخطيط المشروعات الصغيرة والمتوسطة مع تطبيق تلك الاستراتيجية علي قطاع الصناعات الجلدية في مصر وإعداد دراسة جدوى مبدائية بما يخدم فكرة البحث، كما يهدف البحث إلى التعرف على كيفية الوصول إلى مجتمعات صناعية متكاملة، وذلك في ضوء استراتيجية العناقيد الصناعية والتحالفات الاستراتيجية مع التطبيق على قطاع الجلود في مصر. ويختبر البحث الفرض القائل إن يمكن الاستفادة من استراتيجية العناقيد الصناعية والتحالفات الاستراتيجية في الوصول إلى "مجتمعات صناعية متكاملة" تدعم تنافسية قطاع الجلود، وقد جاءت النتائج لتثبت صحة الفرض وأوصت بإتباع المقترح المقدم في البحث في التخطيط الصناعي وتأسيس عدد من التجمعات الصناعية العنقودية الشكل المبين بالبحث.
Keywords: الاقتصاد القومي -- المؤسسات الصناعية -- قطاع الجلود -- مصر